123 Oxidative stress responses – potential biomarkers in multiple sclerosis. Issue 9 (12th August 2022) - Minton, Thomas; Hares, Kelly; Kemp, Kevin; Scolding, Neil; Rice, Claire
Abstract : Introduction: Oxidative stress is implicated in the pathophysiology of multiple sclerosis (MS). To investigate their potential as MS biomarkers, we compared plasma levels of two master regulators of antioxidant processes nuclear factor erythroid 2 related factor 2 (Nrf2) and peroxisome proliferator-activated receptor gamma coactivator 1α (PGC1α), as well as downstream antioxidant enzymes superoxide dismutase 1 (SOD1) and catalase. Methods: Plasma levels of Nrf2, PGC1α and SOD1 were measured using enzyme-linked immunosorbent assay (ELISA). Plasma catalase levels were measured using a catalase activity assay. The results were analysed using a multiple regression model. Results: Plasma PGC1α concentrations were higher in people with MS compared to controls and lower in patients with primary progressive MS than those with relapsing remitting MS. Plasma Nrf2 levels were increased in those on disease modifying therapy with Dimethyl fumarate, which was most pronounced 6 weeks post-initiation. Plasma Nrf2 levels fell in patients commencing Ocrelizumab. Plasma catalase activity was higher in patients with MS when compared to control, and higher in patients with progressive MS phenotypes. No statistically significant changes in plasma SOD1 levels were observed. Conclusions: Our findings support further investigation of the potential for plasma PGC1α, Nrf2 and catalase as disease biomarkers in MS.